A Theoretical Approach on the Strategic Partnership Between the European Union and the Russian Federation - Razvan-Alexandru Gentimir (CES Working Papers, 2015)
The purpose of this paper is to explore the theoretical approaches of the ,,strategic partnership” concept, and then applying them to the relationship and cooperation between the European Union and the Russian Federation, thus emphasizing its evolution. The base of this article lays on a literature review that gathers recent articles and several studies of some researchers in the field, providing some professional information on the subject. Findings reveal that there has not yet got to a general definition of the concepts, researchers and not only would agree upon, and, when applying it to the EU-Russia relation, that there are some mutual benefits as a result of the cooperation. This article shows that, despite of the fact that the startup of the cooperation between the two major global powers was a good one, it now has reached some kind of dead moment, when policy contradictions block the evolution of the partnership.
Keywords: F00; F15; F36; F42; F50; 330; Strategic partnership; cooperation; European Union; Russian Federation; evolution; policy